Cognitive Behavioral Therapy for Depression in Cardiovascular Patients: A Comprehensive Review - Irfan, Uzma (Disease and Health Research: New Insights Vol. 10, 2024)
Globally, the two most common causes of disability in high-income countries are cardiovascular disease (CVD) and depression. These are expected to occur at this level in all income-level countries by 2030. Individuals who have depression are more prone to developing CVD and have a higher mortality rate compared to the general population. Also, cardiovascular disease with depression has been demonstrated to impact the patient’s overall well-being and quality of life. This paper presents an overview of CVD and comorbid depression. It examines how effective cognitive behavioural therapy (CBT) is for depression and evaluates the effectiveness of CBTs for CVD.